Pembelajaran Tematik Berbasis Media Digital untuk Penguatan Perilaku Hidup Sehat, Etika Berbicara, dan Pencegahan Bullying pada Siswa Sekolah Dasar - Dinar Pratiwi; Aisyah Nindya Sari Dewi; Dwi Tisya Nur Faradillah; Muhammad Adrian Maulana; Farid Khomaril Huda; Nailah Putri Azharica Aurellia; Imaniyatin Imaniyatin; Chumi Zahrotul Fitriyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This community service program aimed to improve elementary school students’ understanding and behavior regarding healthy living habits, speaking etiquette, and bullying prevention through thematic learning based on digital media. The program was conducted at SDN Pekalangan 3 for one week with four sessions involving 72 students from grades IV, V, and VI. The methods included socialization, educational games, interactive discussions, and evaluation using pre-tests and post-tests. The results showed an average improvement in students’ understanding scores of 27.4% on health topics, 31.2% on speaking etiquette, and 22.6% on bullying prevention. Behavioral changes were also observed, such as increased handwashing habits, polite language use, and respectful peer interactions. These findings indicate that digital media-based thematic learning is effective in enhancing students’ knowledge and positive behavior. Nevertheless, the program was limited by its short duration and descriptive evaluation approach.